2018
DOI: 10.1007/s10763-018-9907-x
|View full text |Cite
|
Sign up to set email alerts
|

Professional Noticing of Mathematics Teachers: a Comparative Study Between Germany and China

Abstract: Research on teacher noticing in the field of mathematics education research has increased in the last decade; however, only a few studies have investigated the social and cultural impact on teachers' noticing. This paper describes results of an international comparative study on (inservice) mathematics teachers' professional noticing in China and Germany, representing Eastern and Western cultures. In this study, 203 teachers in China and 118 teachers in Germany participated in a video-based assessment of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…A comparative study across a Western and an East Asian context revealed Fig. 1 Modeling teacher competence as a continuum (Blömeke et al 2015a, p. 7) relative strengths of German teachers in noticing from a general pedagogical perspective (P_PID), whereas Chinese teachers were relatively strong in noticing from a mathematics pedagogical perspective (M_PID) (Yang et al 2018).…”
Section: Teachers' Cognitive Skillsmentioning
confidence: 99%
“…A comparative study across a Western and an East Asian context revealed Fig. 1 Modeling teacher competence as a continuum (Blömeke et al 2015a, p. 7) relative strengths of German teachers in noticing from a general pedagogical perspective (P_PID), whereas Chinese teachers were relatively strong in noticing from a mathematics pedagogical perspective (M_PID) (Yang et al 2018).…”
Section: Teachers' Cognitive Skillsmentioning
confidence: 99%
“…translation-back-translation procedures, see also Guidelines for Translating and Adapting Tests, ITC 2017). The findings of this study showed different patterns of strengths and weaknesses of German and Chinese teachers and provide empirical evidence that teacher noticing is influenced by different cultural contexts (Yang et al 2019).…”
Section: The Role Of Cultural Norms For Research On Teacher Noticingmentioning
confidence: 54%
“…This dual sense makes obvious that norms regarding aspects of instructional quality play a double role in teacher noticing research: On the one hand, beyond personal dispositions of teachers (e.g., individual knowledge and beliefs) also cultural norms are assumed to influence teacher noticing (e.g., Yang, Kaiser, König, and Blömeke 2019). On the other hand, such norms form the frame of reference that is already implemented in the operationalization by the researchers.…”
Section: Assessing Teacher Noticingmentioning
confidence: 99%
“…As a matter of fact, Ball (2011) stated that noticing is not objective and it is a perception that develops with cultural values. Therefore, Yang, Kaiser, König and Blömeke (2019) argued that teacher knowledge should not be far from cultural contexts.…”
Section: Discussionmentioning
confidence: 99%